INNOVATIVE APPROACHES TO THE FORMATION AND IMPLEMENTATION OF INTERSECTORAL COOPERATION - Poliakova Yuliia; Stepanov Andriy; Dubil Taras (Видавничий дім "Гельветика", 2024)
The article is concerned with the study of theoretical foundations and practical aspects of formation and development of intersectoral cooperation in world practice. The article considers the existent approaches to the definition of the concept of "intersectoral cooperation", in particular from the standpoint of generating innovative solutions to existing problems, as well as its features and types. It is found that intersectoral cooperation is a constructive and mutually beneficial interaction of three sectors: the state, the business sector and institutions of civil society. The conditions for ensuring effectiveness in the process of establishing intersectoral cooperation are determined. The importance of the communication process as the basis of interaction is emphasised. The institutional structure of intersectoral partnership is outlined, including regulatory principles, mechanisms for implementing the principles and corporate social responsibility. The prerequisites and features of the emergence of intersectoral partnership at the regional level are determined. The experience of foreign countries in the development of intersectoral cooperation in various fields, in particular of the EU member states, is considered.
ІННОВАЦІІЙНІ ПІДХОДИ ДО ФОРМУВАННЯ ТА РЕАЛІЗАЦІЇ МІЖСЕКТОРАЛЬНОГО СПІВРОБІТНИЦТВА
Keywords: intersectoral cooperation; partnership; interaction; public and private partnership; innovative solutions